Speech Acts Types and Psychological Development by Perpetrators and Victims of Sexual Abuse in France: A Psycholingforensic’s Perspective - Dhiba, Arry Devy Farah; Santoso, Bernadus Wahyudi Joko (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. This research examines the relationship between the psychological personalities of perpetrators and victims of sexual abuse in France according to Sigmund Freud's psychoanalytic theory through speech acts delivered by perpetrators and victims in forensic linguistics based on John Searle's speech act theory. Freud's theory emphasizes the dynamics between id, ego, and superego as well as psychosexual personality in psychological development. In this case, there is a statement that has an important meaning in a person's psychological development. Forensic linguistics utilizes language analysis in a legal context, while Searle's speech act theory classifies utterances into assertive, directive, commissive, expressive, and declarative. This research on sexual abuse cases committed by priests in France uses a qualitative descriptive approach to analyze the transcript of the suspect's interrogation through expert psychiatry and the victim's testimony through interviews with French online media journalists uploaded through the RMC Youtube Channel on January 13, 2020. The results show that speech acts in a legal context can significantly affect the psychological state of individuals (suspects and victims). This interdisciplinary approach combines key concepts from psychoanalysis and linguistics that show how language as a communication tool can influence and shape the psychological dynamics of individuals in accordance with the theories of Searle and Freud. This research aims to contribute to a more comprehensive understanding of the interaction between linguistic and psychological factors in a forensic context, with practical implications for a more humanistic approach in the justice system.Keywords: Speech Act, Psychology, Forensic Linguistics, Sexual Abuse